PENDIDIKAN MASYARAKAT SUKU ASLI (STUDI KASUS DUSUN SEJAHTERA DESA KEMBUNG BARU KECAMATAN BANTAN KABUPATEN BENGKALIS PROVINSI RIAU) - Desi Fitriana; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Tribal society belongs to a remote indigenous komonitas in Riau Province. One of them is located in the hamlet of Prosperous villages of Bloated New Sub Regency of Bengkalis Bantan. Quality of people's lives is still very low. This is evidenced by the number of low income communities as well as the level of education also is still low. The level of education of the natives is still very low, and much of the original tribe of children dropping out of school in the school age kejenjang legitimate continuing education as well as higher. This is because of the low level of family economics and lack of facilities and infrastructure that supports the development of the educational aspect in this village. The prosperous village has road access and do not have public transportation as a means of penujang. The meaning of education for tribal people of "important" is marked with the school to school. School education for Tribal communities is important. But still limited with facilities and supporting infrastructure repair so that there are still many children from the natives in the village Prosperous village of Bloated new did not attend school either dropped out of school or not continuing education to a higher level. In the percentage of children continuing education of thirty-nine percent of the children who entered grade school, only eighteen percent of children who continue their education to secondary and only six percent of the children continuing education kejenjang legitimate high school, The remaining thirty-seven per cent of children dropping out of school. Askses a distance far enough for the school to Junior High School and high school for tribal children in the hamlet of prosperous for continuing education to a higher level. As for the implementation of the Government in tackling the problems of tribal society has not been fully realized and distributed evenly in the prosperous village. Keywords: Education Akit Tribe KAT, Bengkalis, Riau